2015
DOI: 10.1021/acs.jpcb.5b04371
|View full text |Cite
|
Sign up to set email alerts
|

Protonation Dynamics and Hydrogen Bonding in Aqueous Sulfuric Acid

Abstract: Hydration of sulfuric acid plays a key role in new-particle formation in the atmosphere. It has been recently proposed that proton dynamics is crucial in the stabilization of these clusters. One key question is how water molecules mediate proton transfer from sulfuric acid, and hence how the deprotonation state of the acid molecule behaves as a function concentration. We address the proton transfer in aqueous sulfuric acid with O K edge and S L edge core-excitation spectra recorded using inelastic X-ray scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
3
27
0
Order By: Relevance
“…Figure 4(b) presents the coefficients of the different spectra with the values from AIMD simulations, and for the higher concentrations the agreement is found to be good. The most likely reason for the mismatch at lower concentration is the quality of the structural AIMD simulation, as we observe large discrepancies between different computational works 14 30 , both of which disagree with the experimental value 39 . We conclude that the lowest concentrations are difficult to simulate due to most likely long reaction times for the span of AIMD.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…Figure 4(b) presents the coefficients of the different spectra with the values from AIMD simulations, and for the higher concentrations the agreement is found to be good. The most likely reason for the mismatch at lower concentration is the quality of the structural AIMD simulation, as we observe large discrepancies between different computational works 14 30 , both of which disagree with the experimental value 39 . We conclude that the lowest concentrations are difficult to simulate due to most likely long reaction times for the span of AIMD.…”
Section: Resultsmentioning
confidence: 55%
“…Secondly, as a more precise but also more challenging approach, we simulated ensemble-averaged S K β emission spectra by sampling the trajectories from previously published AIMD simulations 30 . The protonation distribution along the AIMD runs is presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that in highly concentrated solutions of sulfuric acid (between 75 and 100 %), high contents of undissociated H 2 SO 4 and HSO 4 À are observed (over 73 % of undissociated H 2 SO 4 ). [28] Furthermore, investigations of the proton transfer mechanism in sulfuric acid solutions using (H 2 SO 4 ) n ⋯(H 2 O) m clusters have shown that, at low water concentrations, the assistance of non-deprotonated H 2 SO 4 is mandatory for the stabilization of the conjugate base HSO 4 À and allows deprotonation to occur. [29] According to this hypothesis, the proton would be transferred via a H 2 SO 4 ⋯H 2 SO 4 ⋯B cluster, in which B is any base or solvent [27] molecule present in the mixture capable of accepting the proton.…”
Section: Construction Of the Microsolvation Modelmentioning
confidence: 99%